Can the CutiScan CS 100® measure anisotropy and viscoelasticity in scar tissue after mastectomy? A reliability and validity study. Issue 2 (9th November 2021) - Anthonissen, Mieke; Van den Kerckhove, Eric; Moortgat, Peter; Geraerts, Inge; Devoogdt, Nele; De Vrieze, Tessa; De Groef, An
Abstract: Background: Scars have different biomechanical characteristics, including anisotropy and viscoelasticity compared to healthy skin. To assess these characteristics, the CutiScan CS 100 ® can be used. The aim of the present study is to investigate reliability and validity of this device in breast cancer patients. Materials and methods: Thirty female patients, with scar adhesions following mastectomy were assessed with the CutiScan CS 100 ® . Maximal distensibility (pixels) (V1), after‐suction return rate (pixels) (V2), and their ratio (%) (V3) at three points on and around the scar were assessed as measures of viscoelasticity. For intra‐ and interrater reliabilities, the intra‐class correlation coefficient (ICC) and its 95% confidence intervals were calculated. The standard error of measurement (SEM) was calculated to interpret reproducibility of these measurements. To investigate criterion validity of the measurement of anisotropy, measurements in the direction of healthy skin were compared with measurements in the direction of the scar, using a paired t ‐test. Results: V1, V2, and V3 show poor to moderate intrarater reliability (ICC 0.00–0.72) and interrater reliability (ICC 0.00–0.53). The maximum displacement (V1) on the measurement point above the scar shows the best reliability (ICC 0.33–0.72). The SEM is about the same for all parameters at all three points. The paired sample t ‐test showed a significant difference ( p < 0.05) between V1 in the direction towards the scar versus the measurement towards healthy tissue, on the point below the scar. Conclusion: These first reliability and validity results of the CutiScan CS 100 ® for measuring anisotropy and viscoelasticity in scar tissue adhesions after mastectomy seem promising. Further research is needed addressing the limitations of the present study design.